Constraints to book publishing in Nigeria: a case study of Imo State (2009)
This work is about the challenges faced by Book publishers in Imo State and how these challenges can be overcome. It started by delving into the history of Book publishing in Nigeria and Imo State after which it proceeded by clarifying the concept of publishing. In addition, a profile of Book publishers in the State was made. In order to find out the actual state of Book publishing in Imo State, sun’ey research scheme was employed and questionnaire was used as a major instrument to collect data from thirty publishing houses. The study revealed that majority of publishers in Imo State engaged in publishing tertiary institution books. Also, high cost of imported machinery and raw materials, lack of credit facilities, piracy, poor reading culture, poor quality of locally sourced materials and lack of mechanism put in place to control entry into the profession were identified, among others, as major constraints to book publishing in Imo State. Furthermore, the respondents made submissions on how Book publishing can be promoted in Imo State and by extension, Nigeria. However, the paper concluded and made recommendations on how Book Publishing can help in enhancing scholarship in the State.